The Effect of Working Hourson Health - Berniell, Inés (2018)
Does working time affect workers’ health? We study this question in the context of a French reform which reduced the standard workweek from 39 to 35 hours, at constant earnings. Our empirical analysis exploits varia- tion in the reduction of working time across employers, which was driven by the institutional features of the reform and thus exogenous to workers’ health. We find that longer working hours increase smoking and decrease self-reported health, and that these impacts are concentrated among blue- collar workers. In contrast, white-collar workers’ body mass index increases with hours worked.